Estimation of Lipid Peroxidation Induced by Hydrogen Peroxide in Cultured Human Lymphocytes - Yasir Hasan Siddique; Gulshan Ara; Mohammad Afzal (SAGE Publishing, 2012)
Malondialdehyde (MDA) is used for the estimation of damage by reactive oxygen species. MDA is a major reactive aldehyde resulting from the peroxidation of biological membranes. The most common method used to assess MDA production is the thiobarbituric acid (TBARS) assay. However, the value of this method is curbed by low specificity and has been criticized for its use in human studies. In the present study we have used an alternative method for the estimation of MDA production i.e. reaction of MDA with a chromogenic agent 1-methyl-2-phenylindole at 45°C. The paper describes the method of preparing standards for the estimation of MDA (lipid peroxidation) after the treatment with an oxidative stress inducing agent hydrogen peroxide (H 2 O 2 ). In the present study, the treatments of 1, 5, 10, 20, 50, 100, 150 and 200 μM of H 2 O 2 induced significant increase in lipid peroxidation as compared to the untreated ones. The results suggest that the present method can be used to measure the lipid peroxidation in cultured human peripheral blood lymphocytes and is specific for MDA estimation.